PEMANFAATAN TUMBUHAN DALAM UPACARA ADAT, KESENIAN DAN KEINDAHAN PADA MASYARAKAT KAMPUNG YONGSU DESOYO DISTRIK RAVENI RARA KABUPATEN JAYAPURA - Meike Mandena Maay; Konstantina M.B. Kameubun; Edoward Raunsay (NOVAE GUINEA Jurnal Biologi, 2024)
Papua is a province in Indonesia which is rich in biodiversity, both flora and fauna. This provides a very broad opportunity to be discovered and developed, and used for the welfare of society and also used in ethnic matters. Changes in the way of life of the people in Papua which are increasing rapidly today will have an impact on culture, lifestyle and the preservation of biological natural resources including the preservation of plant species. This study used the observation method, interview method and documentation method. The data obtained was then analyzed descriptively qualitatively. The results showed that the people of Yongsu Desoyo village used plants in traditional ceremonies, art and beauty as many as 18 species from 15 families, which were divided into 7 types of plants for traditional ceremonies, 6 types of plants for art and 5 types of plants for beauty. The parts of the plants used include stems, bark, leaves, flowers, fruits and seeds. The vegetative organs of the leaves dominate the utilization of traditional ceremonies, arts and beauty. The way of processing plants is done in the traditional way according to the knowledge of the community. Efforts to preserve/conserve plants are carried out by cultivating plants that are used in various habitats, such as gardens, fields, and around the yards of residents' houses. Keywords: Utilization of Plants, Traditional ceremonies, Art, Beauty